Brazil: rapid development, internationalization, and middle class formation - Cavusgil, S. Tamer; Kardes, Ilke (Internext, 2013)
Some three decades ago, the business world was focused strictly on such post-industrial economies as the U.S., Germany, UK, and Japan. It was thought that there was no place beyond the western markets. Fast forward to today, the marketplace has been transformed radically. The forces of globalization brought about a highly competitive and crowded landscape, featuring numerous new players from the so-called Emerging Markets (better referred to as ‘growth markets’ since the most common element of these rapidly transforming economies is sustained growth). The center of economic gravity has now shifted to east Asia. Yesterday’s poor and developing countries have profited from the globalized information and communication technologies. These countries have been experiencing rapid pace of economic development, market liberalization, industrialization, modernization, and urbanization.